Parallel aeroacoustic computation of unsteady transonic weapon bay using detached‐eddy simulation via open computational fluid dynamics source codes - Fadil, Ali Can; Zafer, Baha (Wiley, 2023)
SummaryCavity flow research has been ongoing experimentally since the 1940s, especially for weapon bay use in fighter aircraft. Technology advancement has led to the beginning of simulations of experimental studies. The success of these simulations has increased with the emergence of High‐Performance Clusters, and simulation studies have started to take the role of experimental studies. In this paper, an open rectangular, unsteady transonic cavity with a length to depth ratio of 5, Mach number 0.85 and Reynolds number of approximately 6.5 × 106 is simulated using Computational Fluid Dynamics (CFD) on a High‐Performance Cluster. Likewise, cavity door is used to model a real weapon bay. Detached‐Eddy Simulation is used to resolve turbulent properties in the flow domain. Results compatible with experimental data are obtained with OpenFOAM, an open‐source CFD code based on the finite volume method. Additionally, computational costs are given in the clock‐time analysis section, and the necessity of high‐performance clusters for CFD and Computational Aeroacoustics studies is emphasized.